Meningkatkan Kecerdasan Digital dalam Dinamika Pendidikan Kristiani di era Pascakebenaran: Sebuah Perspektif Kolose 4:5 - Leiwakabessy, Tabita; Purwonugroho, Daniel Pesah (SIKIP: Jurnal Pendidikan Agama Kristen, 2024)
This article explores the dynamics of Christian religious education in the post-truth era and its relationship with the enhancement of digital intelligence from the perspective of Colossians 4:5. Christian religious education embodies the truth of God's Word. Such education is essential for students in this post-truth era. The post-truth era introduces a distortion of reality in society, degrading the value of truth by reducing it to personal taste without verifiable and accountable affirmation. Students are expected to possess digital intelligence in this post-truth era. Digital intelligence is cultivated through Christian religious education within the framework of Colossians 4:5. Utilizing a descriptive qualitative approach; this study investigates the enhancement of digital intelligence from the perspective of Colossians 4:5 through Christian education in the post-truth era. Colossians 4:5 provides an appropriate perspective to develop students' digital intelligence through Christian education to face the challenges of the post-truth era.  AbstrakArtikel ini dibuat untuk menelusuri dinamika pendidikan agama Kristen di era pascakebenaran dan hubungannya dengan peningkatan kecerdasan digital dalam perspektif Kolose 4:5. Pendidikan agama Kristen merupakan pendidikan dengan nilai kebenaran Firman Tuhan. Pendidikan kristiani diperlukan oleh peserta didik di era pascakebenaran ini. Era pascakebenaran memberikan sebuah distorsi kebenaran dalam kehidupan masyarakat. Era pascakebenaran mendegradasi nilai kebenaran karena kebenaran hanyalah perkara selera perspektif personal tanpa adanya verifikasi dan affirmasi yang dapat dipertanggung jawabkan. Peserta didik diharapkan memiliki kecerdasan digital dalam era pascakebenaran ini. Kecerdasan digital dibangun melalui pendidikan agama Kristen dalam perspektif Kolose 4:5. Melalui pendekatan kualitatif deskriptif, penelitian ini akan menelusuri peningkatan kecerdasan digital dalam perspektif Kolose 4:5 melalui pendidikan kristiani di era pascakebenaran ini. Kolose 4:5 merupakan perspektif yang tepat untuk membangun kecerdasan digital peserta didik melalui pendidikan kristiani untuk menghadapi era pascakebenaran ini.